"Cycling of amino‐nitrogen and other nutrients between shoots and roots in cereals—A possible mechanism integrating shoot and root in the regulation of nutrient uptake" by H.D. Cooper and D.T. Clarkson, Journal of Experimental Botany (1989) 40:753–762. Issue 5 (23rd June 2020) - Rufty, Thomas W.; Sinclair, Thomas R.
Abstract: This article is part of a series of brief commentaries to highlight papers that have resulted in important and distinctly new perspectives in crop science. A criterion for selection of papers is that they must have been published at least 20 yr ago to allow for a long‐range perspective in assessment of the papers. The current article briefly reviews the paper by H.D. Cooper and D.T. Clarkson published in 1989 that offered an original analysis of internal movement of nitrogen in wheat ( Triticum aestivum L.). Using 15 NO3 − fed to a split‐root system, they found that a large fraction of absorbed nitrogen was rapidly cycled around the plant as a result of exchanges between the xylem and phloem. They concluded that cycling in the plant ensured tissues had access to a common pool of soluble nitrogen from which nitrogen could be removed and incorporated into protein depending on the demands of tissue growth. The cycling pool of nitrogen also provided a possible whole‐plant signaling mechanism that coordinates growth activities with the feedback control system regulating nitrate uptake by the root.